2023
DOI: 10.3390/metabo13010087
|View full text |Cite
|
Sign up to set email alerts
|

Links between Metabolic Syndrome and Hypertension: The Relationship with the Current Antidiabetic Drugs

Abstract: Hypertension poses a significant burden in the general population, being responsible for increasing cardiovascular morbidity and mortality, leading to adverse outcomes. Moreover, the association of hypertension with dyslipidaemia, obesity, and insulin resistance, also known as metabolic syndrome, further increases the overall cardiovascular risk of an individual. The complex pathophysiological overlap between the components of the metabolic syndrome may in part explain how novel antidiabetic drugs express plei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 150 publications
1
12
0
1
Order By: Relevance
“…The present study found a high prevalence of the combinations of hypertension + diabetes, hypertension + stroke, and hypertension + CHD. Hypertension and diabetes are the main components of metabolic syndrome and share pathophysiological mechanisms ( 21 ). Hypertension is the primary risk factor for cardiovascular diseases such as CHD and stroke, making it likely that these conditions occur together.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found a high prevalence of the combinations of hypertension + diabetes, hypertension + stroke, and hypertension + CHD. Hypertension and diabetes are the main components of metabolic syndrome and share pathophysiological mechanisms ( 21 ). Hypertension is the primary risk factor for cardiovascular diseases such as CHD and stroke, making it likely that these conditions occur together.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome affects not only the urinary system but also various other bodily systems. Researchers have examined the connection between metabolic syndrome and the severity and frequency of lower urinary tract symptoms (LUTS) (3). The association between voiding and storage symptoms with metabolic syndrome involves understanding the underlying pathological mechanisms related to atherosclerosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…It has gained significant attention recently because of its link to cardiovascular diseases and type 2 diabetes. However, its role in urological conditions like BPH and LUTS is increasingly recognized (3).…”
Section: Introductionmentioning
confidence: 99%
“…These novel anti-hyperglycemic agents possess multiple pleiotropic effects, particularly, for SGLT-2i and GLP-1RA. Previous studies have reported that in addition to controlling blood glucose levels, these agents also have significant beneficial impacts on cardiovascular protection, renal protection, and improvement of cognitive function ( 18 20 ). However, no studies in China have reported the influence of early treatment with these novel anti-hyperglycemic agents on the legacy effect of poor early glycemic control.…”
Section: Introductionmentioning
confidence: 99%